2016
DOI: 10.5234/cnpt.7.20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Blonanserin and Paliperidone in 93 In-patients with Acute- to Maintenance-phase Schizophrenia

Abstract: When initiating treatment for acute-phase schizophrenia, careful consideration needs to be given to which drug will be used in the subsequent maintenance phase. Since blonanserin (BNS) and paliperidone (PAL) are both first-line treatments for acute-phase schizophrenia, our study retrospectively investigated the treatment continuation rate, dose levels, use of concomitant medications, clinical effects, and adverse drug reactions in 93 acute-phase schizophrenia patients receiving either of the monotherapies (BNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…The pituitary gland, which secretes hormones including prolactin, exists outside the blood-brain barrier (BBB). With blonanserin treatment, the brain/pituitary (B/P) ratio, calculated from the D2 receptor occupancy in the temporal lobe and the pituitary gland, showed that the percentage of drug crossing the BBB was greater than that of other antipsychotics [49]. This feature of blonanserin suggests that it may have considerable ability to distribute to the brain with a therapeutic efficacy that does not cause hyperprolactinaemia and problematic endocrine effects.…”
Section: Discussionmentioning
confidence: 99%
“…The pituitary gland, which secretes hormones including prolactin, exists outside the blood-brain barrier (BBB). With blonanserin treatment, the brain/pituitary (B/P) ratio, calculated from the D2 receptor occupancy in the temporal lobe and the pituitary gland, showed that the percentage of drug crossing the BBB was greater than that of other antipsychotics [49]. This feature of blonanserin suggests that it may have considerable ability to distribute to the brain with a therapeutic efficacy that does not cause hyperprolactinaemia and problematic endocrine effects.…”
Section: Discussionmentioning
confidence: 99%